Impaired oral health: a required companion of bacterial aspiration pneumonia - Ashford, John R. (Frontiers in Rehabilitation Sciences, 2024)
Laryngotracheal aspiration has a widely-held reputation as a primary cause of lower respiratory infections, such as pneumonia, and is a major concern of care providers of the seriously ill orelderly frail patient. Laryngeal mechanical inefficiency resulting in aspiration into the lower respiratory tract, by itself, is not the cause of pneumonia. It is but one of several factors that must be present simultaneously for pneumonia to develop. Aspiration of oral and gastric contentsoccurs often in healthy people of all ages and without significant pulmonary consequences. Inthe seriously ill or elderly frail patient, higher concentrations of pathogens in the contents of theaspirate are the primary catalyst for pulmonary infection development if in an immunocompromised lower respiratory system. The oral cavity is a complex and ever changing eco-environment striving to maintain homogeneity among the numerous microbial communities inhabiting its surfaces. Poor maintenance of these surfaces to prevent infection can result inpathogenic changes to these microbial communities and, with subsequent proliferation, can altermicrobial communities in the tracheal and bronchial passages. Higher bacterial pathogen concentrations mixing with oral secretions, or with foods, when aspirated into an immunecompromised lower respiratory complex, may result in bacterial aspiration pneumonia development, or other respiratory or systemic diseases. A large volume of clinical evidence makes it clear that oral cleaning regimens, when used in caring for ill or frail patients in hospitals and long-term care facilities, drastically reduce the incidence of respiratory infection and death. The purpose of this narrative review is to examine oral health as a required causative companionin bacterial aspiration pneumonia development, and the effectiveness of oral infection control inthe prevention of this disease.